PEMERIKSAAN Escherichia coli, Staphylococcus aureus DAN Salmonella PADA ES JUS JERUK - Dini Meilisnawaty; Dwi Suryanto; Ida Fauziah (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
The research was carried out to observe the existence of Escherichia coli, Staphylococcus aureus and Salmonella in orange juice sold at setiabudi street, Medan. Descriptive analysis to 10 samples which examined in Balai Laboratorium Kesehatan, Medan showed that 3 of them contaminated by E.coli. The number of E.Coli found in the samples are above the standard issued by DEPKES RI 1991. Contamination by S. aureus and Salmonella were not found. Bacteria Total Plate Count value announced that there were some other species exist in the samples.